Creating a Sense of Belonging in the Academy: An Example of a Métis-Centred Space - Delgado, Lucy; Forsythe, Laura (Engaged Scholar Journal, 2025)
As post-secondary institutions continue the slow move towards indigenization and reconciliation, more Indigenous-centred spaces are created. But how many of those spaces are Nation-specific? In this article, we describe one example of a Nation-specific gathering, the Métis Research Symposium, and the impact that the gathering had on the mostly-Métis audience, including the enhanced sense of belonging and connection that the respondents reported. We advocate for institutions and administrators to shift towards creating more Nation-specific opportunities for students, faculty, and staff at all levels.